2008
DOI: 10.1016/j.juro.2008.03.142
|View full text |Cite
|
Sign up to set email alerts
|

Tolterodine Extended Release Attenuates Lower Urinary Tract Symptoms in Men With Benign Prostatic Hyperplasia

Abstract: Treatment with tolterodine ER in men with BPH and LUTS may be a reasonable therapeutic option as initial therapy or after failed treatment with alpha-blockers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 18 publications
1
24
0
2
Order By: Relevance
“…However, several studies have reported that prescribing anti-muscarinic agents to men with LUTS or even BOO does not seem to elevate the risk of AUR [11,40]. The results of several studies support the efficacy and safety of antimuscarinics in treating men with LUTS and OAB [4144]. For example, Abrams et al [11] reported the efficacy of tolterodine immediate-release in men with both BOO and OAB.…”
Section: Antimuscarinic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have reported that prescribing anti-muscarinic agents to men with LUTS or even BOO does not seem to elevate the risk of AUR [11,40]. The results of several studies support the efficacy and safety of antimuscarinics in treating men with LUTS and OAB [4144]. For example, Abrams et al [11] reported the efficacy of tolterodine immediate-release in men with both BOO and OAB.…”
Section: Antimuscarinic Agentsmentioning
confidence: 99%
“…In recent years, a number of studies have reported on the combination treatment of alpha receptor antagonists and antimuscarinic agents [12,4147]. In a 2006 study by Kaplan et al [48] named the TIMES study, tolterodine extend release (ER) and tamsulosin combination treatment resulted in significant improvement in urgency episodes, number of micturitions, nocturia, and IPSS.…”
Section: Combination Treatment: Alpha Receptor Antagonists + Antimuscmentioning
confidence: 99%
“…A recent open-label study evaluated the safety and efficacy of extended-release tolterodine in 43 men with lower urinary tract symptoms because of benign prostatic enlargement and in whom -blocker therapy had failed previously [34]. At 6 months the AUA symptom score improved from 17.3 at baseline to 11.2 at 6 months (-6.1, P < 0.001).…”
Section: Urinary Retentionmentioning
confidence: 99%
“…Data suggest that antimuscarinic agents are safe and effective in treating storage symptoms in men with LUTS [9][10][11][12][13]. However, there is skepticism regarding their use because of the concern of an increased risk of urinary retention [14].…”
Section: Introductionmentioning
confidence: 99%